2004
DOI: 10.1248/bpb.27.1168
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism and Physiological Role of Cytosolic Phospholipase A2

Abstract: Cytosolic phospholipase A 2 a a (cPLA 2 a a) preferentially hydrolyzes phospholipids containing arachidonic acid and plays a key role in the biosynthesis of eicosanoids. This review discusses the essential features of cPLA 2 a a regulation and addresses new insights into the functional properties of this enzyme. Full activation of the enzyme requires Ca 2؉ binding to an N-terminal C2 domain and phosphorylation on serine residues. Ca 2؉ binding induces translocation of cPLA 2 a a from the cytosol to the perinuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
185
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(197 citation statements)
references
References 98 publications
7
185
0
5
Order By: Relevance
“…Cell stimulation by a variety of agonist receptors leads to the activation of another PLA 2 form, the group IVA, calcium-dependent cytosolic PLA 2 a (cPLA 2 a), which then becomes the dominant PLA 2 involved in AA release (15)(16)(17)(18)(19). Under stimulation conditions, the rate of AA release clearly exceeds that of reincorporation into PLs, hence net accumulation of AA occurs that is followed by its conversion into different eicosanoids.…”
mentioning
confidence: 99%
“…Cell stimulation by a variety of agonist receptors leads to the activation of another PLA 2 form, the group IVA, calcium-dependent cytosolic PLA 2 a (cPLA 2 a), which then becomes the dominant PLA 2 involved in AA release (15)(16)(17)(18)(19). Under stimulation conditions, the rate of AA release clearly exceeds that of reincorporation into PLs, hence net accumulation of AA occurs that is followed by its conversion into different eicosanoids.…”
mentioning
confidence: 99%
“…The primary means by which AA is released from membranes is the agonist induced activation of the calcium dependent group IV  isoform of cPLA 2 , due to its high specificity and selectivity for glycerophospholipids containing AA at the sn-2 position. Although the agonist induced activation of cPLA 2  has been established as the rate limiting step of eicosanoid biosynthesis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), the deacylation of diacylglycerol (DAG) via DAG lipase also produces AA for the synthesis of eicosianoids. In addition, DAG lipase has been suggested to mediate the release of AA in KCs (56,62).…”
Section: Discussionmentioning
confidence: 99%
“…In the same model, we have also shown that the fibrotic stress primes KCs for the release of TXA 2 by inducing the upregulation of cytosolic phopholipase A 2 (cPLA 2 ), COX-2, and thromboxane synthase (TS) (10), the three key enzymes for its biosynthesis (11)(12)(13)(14)(15)(16). cPLA 2 is critical for the production of AA-derived eicosanoids due to its high specificity and selectivity for glycerophospholipids containing AA at the sn-2 position (17)(18)(19). The significance of cPLA 2 in eicosanoid production is further evident as cells and tissues from cPLA 2 -deficient mice fail to produce prostaglandins, leukotrienes, and thromboxanes (20,21).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…cPLA 2 α (group IVA) plays a pivotal role in providing AA because of its selectivity for phospholipds containing AA at the sn-2 position (4, 10). In group IV, cPLA 2 β (IVB), and cPLA 2 γ (IVC) require Ca 2+ for their activity, and newly identified isoforms of cPLA 2 including δ, ε, and ζ subtypes did not appear to have a preference for AA in phospholipids (10,11). So far, the Ca 2+ -independent PLA 2 (group VIA and VIB) family and some of the Group IV family show Ca 2+ -independent activity (12,13).…”
Section: Introductionmentioning
confidence: 99%